Penguatan Profil Pelajar Rahmatan Lil ‘Alamin Melalui Eksplorasi Kearifan Lokal di Mas Miftahussalam Medan - Manshuruddin, Manshuruddin (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
The Rahmatan lil ‘Alamin Student Profile (PPRA) is a strategic initiative by the Indonesian Ministry of Religious Affairs aimed at fostering inclusive, moderate, and character-oriented madrasah students. This community service activity aimed to contextualize PPRA values through the exploration of Nusantara’s traditional culinary heritage at MAS Miftahussalam Medan, focusing on inclusivity and openness to cultural diversity. Conducted over two days, the program employed a project-based learning approach involving lecturers, university students, and madrasah students in three key sessions: value-based lectures, local wisdom workshops, and culinary presentations. Students explored moral values embedded in traditional dishes such as es kuwut, rujak nusantara, mie pecel, and es sarang burung. Evaluation was carried out qualitatively through participatory observation and guided reflection. The findings indicated that the program enhanced students’ reflective understanding of Rahmatan lil ‘Alamin values while fostering tolerance, responsibility, and cultural discernment. In addition to enriching students’ character formation, the program offered contextual pedagogical experiences for university students and strengthened collaboration between higher education and madrasah institutions. This model presents a replicable and relevant approach to Islamic character education rooted in local wisdom and applicable in responding to cultural diversity within educational settings.ABSTRAKProgram Penguatan Profil Pelajar Rahmatan lil ‘Alamin (PPRA) merupakan inisiatif strategis Kementerian Agama untuk membentuk pelajar madrasah yang inklusif, moderat, dan berkarakter. Kegiatan pengabdian ini bertujuan menanamkan nilai-nilai PPRA secara kontekstual melalui eksplorasi budaya kuliner Nusantara di MAS Miftahussalam Medan, dengan fokus pada nilai inklusivitas dan keterbukaan terhadap budaya lain. Selama dua hari, kegiatan dilaksanakan dengan pendekatan project-based learning yang melibatkan dosen, mahasiswa, dan siswa dalam tiga sesi utama: penyampaian materi, workshop nilai lokal, dan presentasi kuliner. Siswa dikenalkan pada nilai-nilai karakter dari makanan tradisional seperti es kuwut, rujak nusantara, mie pecel, dan es sarang burung. Evaluasi dilakukan secara kualitatif melalui observasi partisipatif dan refleksi terbimbing. Hasilnya menunjukkan bahwa kegiatan ini mampu meningkatkan pemahaman siswa terhadap nilai-nilai Islam rahmatan lil ‘alamin secara reflektif, serta membentuk sikap toleran, bertanggung jawab, dan selektif dalam menyikapi budaya lokal. Selain itu, kegiatan ini juga memberikan pengalaman pedagogis kontekstual bagi mahasiswa dan mempererat kolaborasi antara perguruan tinggi dan madrasah. Model ini dapat direplikasi sebagai strategi pembelajaran karakter Islami yang aplikatif dan relevan dalam menghadapi keberagaman budaya.